HIV/AIDS, growth and poverty in KwaZulu-Natal and South Africa: Integrating firm-level surveys with demographic and economywide modeling - Thurlow, James; George, Gavin; Gow, Jeff (International Food Policy Research Institute, 2009)
This paper estimates the economic impact of HIV/AIDS on KwaZulu-Natal (KZN) and the rest of South Africa (RSA). We extend previous studies by employing an integrated analytical framework that combines the following: firm-level surveys of workers’ HIV prevalence by sector and occupation; a demographic model that produces both population and workforce projections; and a regionalized economywide model linked to a survey-based micro-simulation module. This framework permits a full macro-microeconomic assessment. The results indicate that HIV/AIDS greatly reduces annual economic growth, mainly by lowering the long-term rate of technical change. However, the impacts on income poverty are small, and inequality is reduced by HIV/AIDS. This is because high unemployment among low-income households minimizes the economic costs of increased mortality. In contrast, slower economic growth hurts higher-income households despite the lower prevalence of HIV among these households. We conclude that the increase in economic growth achieved through addressing HIV/AIDS is sufficient to offset the population pressure this move will place on income poverty. Moreover, incentives to mitigate HIV/AIDS lie not only with poorer infected households, but also with uninfected higher-income households. Our findings reveal that HIV/AIDS will place a substantial burden on future economic development in KZN and RSA, confirming the need for policies to curb the economic costs of this pandemic.